Descriptive Analysis of Associated Factors for Urgent Versus Nonurgent Inpatient Spine Transfers to a Tertiary Care Hospital. (November 2018) - Schroeder, Gregory D.; McKenzie, James C.; Casper, David S.; Stake, Seth; Buchholz, Joseph; Kepler, Chris; Rihn, Jeffery A.; Woods, Barret I.; Radcliff, Kris E.; Kaye, I. David; Nicholson, Kristen; Anderson, D. Greg; et al.
Patients with spine-associated symptoms are transferred regularly to higher levels of care for operative intervention. It is unclear what factors lead to the transfer of patients with spine pathology to level I care facilities, and which transfers are indicated. All patients with isolated spinal pathology who were transferred from 2011 to 2015 were reviewed. Patients were divided into urgent transfers, defined as anyone who required operative intervention, and nonurgent transfers. Two hundred twenty-seven patients were transferred for isolated spinal pathology over 51 months; 109 (48.0%) patients required urgent intervention and 118 (52.0%) patients required nonurgent care. No significant differences were found between groups in terms of private insurance, age, sex, race, or Charlson comorbidity index. The urgent group was less likely to have a traumatic chief complaint (57.8% vs 78.0%, P = .001). More than half of all spine patients who were transferred to a tertiary care center required minimal intervention.